2014
DOI: 10.3390/w6092830
|View full text |Cite
|
Sign up to set email alerts
|

Improving Irrigated Lowland Rice Water Use Efficiency under Saturated Soil Culture for Adoption in Tropical Climate Conditions

Abstract: Saturated soil culture is one of the water saving techniques that can improve water productivity. However, it is either less implemented or adopted because it consumes more time and energy. Therefore, an experiment was conducted to determine the effective water depth that can keep soil moisture close to saturation for a commonly practiced irrigation interval, combined with a rainfall pattern for increasing water productivity. The design was a randomized complete block with three replications and four water tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…In addition, root volume was heaviest in plants grown under three-day intermittent irrigation intervals. Greater root volume and longer roots is regarded as an adoption measure for plants to maximize water capture and access water at grater depths [36,51]. Even though root dry biomass produced similar results, it was highest under intermittent irrigation of three-day interval, which could indicate a strong water and nutrient absorption capacity translating into high grain production.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, root volume was heaviest in plants grown under three-day intermittent irrigation intervals. Greater root volume and longer roots is regarded as an adoption measure for plants to maximize water capture and access water at grater depths [36,51]. Even though root dry biomass produced similar results, it was highest under intermittent irrigation of three-day interval, which could indicate a strong water and nutrient absorption capacity translating into high grain production.…”
Section: Discussionmentioning
confidence: 72%
“…The 20 uppermost fully expanded leaves were selected from the randomly selected hills with three observations made per leaf for chlorophyll content analysis among treatments. Analysis of leaves sampling patterns done by [36,37] showed that at least four leaves per plot are needed, with several observations per leaf. Then, the average of these observations was used to represent the leaf chlorophyll content.…”
Section: Plant Height Tiller Numbers and Chlorophyllmentioning
confidence: 99%
“…However, the processes of transplanting younger seedlings should be carried out in a well-designed and levelled field to avoid irregular distribution of irrigation water that may lead to the submergence of the transplanted seedlings that consequently result to premature crop failure [10]. These and many technological aspects enhance sustainable high yield per unit area of rice production [11]. However, this technology requires high reliability of water so as to facilitate physiological and nutritional maintenance of the fields [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the root volume weight of intermittent irrigation was higher too. Greater root volume and longer roots are regarded as an adoption measure for plants to maximize water capture and access water at greater depths (Ascha, 2005 ;Kima et al, 2014).…”
Section: Total Length Of Rootmentioning
confidence: 99%